Chrono-Proteomics of Human Saliva: Variations of the Salivary Proteome during Human Development - Messana, Irene; Cabras, Tiziana; Iavarone, Federica; Manconi, Barbara; Huang, Liling; Martelli, Claudia; Olianas, Alessandra; Sanna, Maria Teresa; Pisano, Elisabetta; Sanna, Monica; Arba, Morena; D’Alessandro, Alfredo; et al. (Journal of proteome research, 2015)
An important contribution to the variability of any proteome is given by the time dimension that should be carefully considered to define physiological modifications. To this purpose, whole saliva proteome was investigated in a wide age range. Whole saliva was collected from 17 preterm newborns with a postconceptional age at birth of 178–217 days. In these subjects sample collection was performed serially starting immediately after birth and within about 1 year follow-up, gathering a total of 111 specimens. Furthermore, whole saliva was collected from 182 subjects aged between 0 and 17 years and from 23 adults aged between 27 and 57 years. The naturally occurring intact salivary proteome of the 316 samples was analyzed by low- and high-resolution HPLC–ESI–MS platforms. Proteins peculiar of the adults appeared in saliva with different time courses during human development. Acidic proline-rich proteins encoded by PRH2 locus and glycosylated basic proline-rich proteins encoded by PRB3 locus appeared following 180 days of postconceptional age, followed at 7 months (±2 weeks) by histatin 1, statherin, and P–B peptide. The other histatins and acidic proline-rich proteins encoded by PRH1 locus appeared in whole saliva of babies from 1 to 3 weeks after the normal term of delivery, S-type cystatins appeared at 1 year (±3 months), and basic proline-rich proteins appeared at 4 years (±1 year) of age. All of the proteinases involved in the maturation of salivary proteins were more active in preterm than in at-term newborns, on the basis of the truncated forms detected. The activity of the Fam20C kinase, involved in the phosphorylation of various proteins, started around 180 days of postconceptional age, slowly increased reaching values comparable to adults at about 2 years (±6 months) of age. Instead, MAPK14 involved in the phosphorylation of S100A9 was fully active since birth also in preterm newborns.